Gap analysis of water governance in Northern Iran: A closer look into the water reservoirs. Issue 77 (November 2017) - Mirzaei, Arezoo; Knierim, Andrea; Fealy Nahavand, Saeid; Mahmoudi, Hossein
Highlights: A multi-level approach is required for water governance. Addressing governance gaps in water sector is crucial in terms of achievement of good governance. Lack of a specific law for water reservoirs is the most acute gap among all. Reforming and updating the country's water law are needed for good water governance. Abstract: The amount of rainfall in Mazandaran province of Northern Iran is high. Mazandaran has man-made water reservoirs called Ab-bandan, to collect rainfall for irrigating rice farms during the growing seasons. However, rice farms face water scarcity because only a small amount of rainfall is being stored in Ab-bandans, while either the remaining water runs off into the sea, or causes water-logging or flooding. This research addresses Ab-bandan s governance gaps in the Mazandaran province, using the 'Multi-level Governance Framework' introduced by the Organization for Economic Co-operation and Development (OECD). A modified Delphi technique with face-to-face interviews and a ranking round is used to identify Ab-bandan s governance gaps. The identified gaps are classified into seven categories by applying the OECD's framework. In each of the categories there is one most important gap: the lack of a specific law for Ab-bandans, lack of long-term and strategic planning, low recognition of Ab-bandans at the national level, insufficient budget, lack of water user associations, lack of research in practice, and lack of using technology. The findings show that lack of a specific law for Ab-bandan s in the country's water law is the most acute gap of all. In addition, the analysis highlights the fact that the policy category is the most critical one. The identified gaps are interlinked and exacerbate each other, therefore, a holistic perspective is needed to understand and resolve them. This study recommends a reform in the country's water law, improved linkage between levels of government, co-operation among organizations involved in Ab-bandan s management, and participation of local stakeholders in planning.